The Influence of Principal’s Supervision on the Pedagogic Competence of Teachers - Maryati, Yenny (PPSDP International Journal of Education, 2024)
This study aims to find out whether there is an influence between the supervision of the principal on the pedagogic competence of teachers at SMA Negeri 1 Talang Kelapa. This is descriptive quantitative research by looking at the causal relationship between variables to the object to be studied. The method used is a survey method where data were collected from a large number of respondents through questionnaires. The population in this study is teachers of SMA Negeri 1 Talang Kelapa with sampling using probability sampling techniques, where the samples taken are carried out randomly so that the population gets the same opportunity to be selected as a sample. The hypothesis test was carried out using a simple linear regression test. From the results of the study, it was found that there was a significant influence of 55.1% of the principal’s supervision on the pedagogic competence of teachers, while the remaining 44.9% was influenced by other factors other than the variables in this study.